2020
DOI: 10.1016/j.arthro.2020.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Evidence to Support Surgical Intervention for First-Time Shoulder Instability: Stabilize Them Early!

Abstract: Historically, a primary anterior instability event has been treated nonoperatively. In the literature, a multitude of outcome scores and definitions for recurrence of instability complicates the interpretation and synthesis of evidencebased recommendations. However, there is an emerging body of high-quality evidence that early surgical stabilization yields better overall outcomes. A wait-and-see approach would be acceptable if it was without detrimental effects, but there is a cost to recurrence of instability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…There is an increasing body of evidence demonstrating excellent RTS outcomes after surgical intervention for shoulder instability. 6 , 7 , 28 , 38 , 39 Despite advances in surgical technique and rehabilitation, there is a persistent cohort of patients who are unable to achieve a full RTS after shoulder surgery. 12 We posit that psychological factors are a key contributor among this cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an increasing body of evidence demonstrating excellent RTS outcomes after surgical intervention for shoulder instability. 6 , 7 , 28 , 38 , 39 Despite advances in surgical technique and rehabilitation, there is a persistent cohort of patients who are unable to achieve a full RTS after shoulder surgery. 12 We posit that psychological factors are a key contributor among this cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
“…between 70% and 95%. [31][32][33][34][35][36][37][38][39][40][41][42][43] However, the estimates of the rate of return to preinjury levels of activity and competition are currently limited, potentially due to a lack of activity-level assessment standardization. 22,30,37 A recent meta-analysis identifying studies reporting RTS after surgery for shoulder instability found that, on average, 73% of people returned to any sport and 65% returned to their preinjury level of sport.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the risk factors for recurrence are Young age, Glenoid bone loss, Hill-Sach lesion (seen in 93% of 1st time di slocators), ligamentous la x it y, multidirectional instability, prior ipsilateral dislocation, and contact or overhead sports participation [30]. Diffusely small labral morphology and increased number of preoperative dislocations before Bankart repair was associated with increased odds recurrent instability after surgery [31]. One must remember that there are some contraindications to primary repair like epilepsy, Multidirectional laxity and instability, other medical comorbidities , inabilit y to follow rehabilitation programme, and voluntary dislocators.…”
Section: Treatmentmentioning
confidence: 99%